Preparedness and Preventive Practices for Lassa Fever Transmission among Health Care Workers in Bauchi LGA, Bauchi State, Nigeria - Limanci, Mahmood Sunusi; Mohammed, Ibrahim Babangida; Saidu, Mustapha; Saleh, Rakiya; Abdullahi, Mohammed Idrees; Margaret, IDOWU Oluwatoyin (American Journal of Biology and Natural Sciences, 2025)
Background: Lassa fever remains a significant public health threat in Nigeria, particularly among healthcare workers (HCWs) who face high occupational risks due to frequent exposure. Despite increasing government and institutional efforts to curb transmission, gaps in preparedness and preventive practices persist in endemic regions, raising concerns about healthcare system resilience. Objective: This study assessed the level of knowledge, preventive practices, and preparedness for Lassa fever prevention among healthcare workers in Bauchi Local Government Area (LGA), Bauchi State, Nigeria. Method of Analysis: A descriptive cross-sectional survey was conducted among 150 healthcare workers across primary, secondary, and referral facilities. Data were collected using a structured questionnaire and presented using frequency and percentage distributions. Associations between knowledge, preventive practices, and preparedness levels were analyzed and interpreted in line with standard epidemiological reporting. Results: The findings revealed that 61.3% of respondents demonstrated adequate knowledge of managing Lassa fever cases, and all agreed that laboratory staff and health workers are vulnerable to infection. Preventive practices showed that 65.3% acknowledged that prevention was linked to knowledge, and 61.3% reported regular use of personal protective equipment (PPE), although 59.3% noted inadequate supplies of safety materials. Preparedness assessment indicated that 66.7% of HCWs reported improvisation during shortages, 69.3% affirmed the availability of isolation spaces, and 79.3% agreed that adequate preventive measures were in place to reduce future transmission. Socio-demographic analysis showed that most HCWs were between 30–39 years (36.7%), predominantly nurses (33.3%), with the majority working in primary healthcare facilities (60%). Conclusion: Although healthcare workers in Bauchi LGA demonstrated a relatively high level of knowledge and preparedness regarding Lassa fever, gaps persist in preventive practices, particularly in the consistent use and availability of safety materials. Strengthening supply chains, expanding infection prevention and control training, and improving facility-level preparedness remain critical for mitigating occupational risks and preventing transmission among HCWs in Lassa fever–endemic regions.